2020
DOI: 10.1038/s41467-020-18345-4
|View full text |Cite
|
Sign up to set email alerts
|

Defect and structural evolution under high-energy ion irradiation informs battery materials design for extreme environments

Abstract: Understanding defect evolution and structural transformations constitutes a prominent research frontier for ultimately controlling the electrochemical properties of advanced battery materials. Herein, for the first time, we utilize in situ high-energy Kr ion irradiation with transmission electron microscopy to monitor how defects and microstructures evolve in Na- and Li-layered cathodes with 3d transition metals. Our experimental and theoretical analyses reveal that Li-layered cathodes are more resistant to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 91 publications
0
17
0
Order By: Relevance
“…15 Our further study discovered that high-energy ion radiation can create dislocations controllably in both density and distribution in Li-and Na-layered cathodes. 20 We expect that controlling structural defects through high-energy ion radiation can offer an effective path toward tailoring electrochemical properties of battery materials. In addition, a Ni−Li antisite defect is universally observed in layer oxide cathodes during synthesis and electrochemical cycling, which hinders Li transport and reduces capacity.…”
Section: Recent Progress In Understanding Heterogeneity and Structura...mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Our further study discovered that high-energy ion radiation can create dislocations controllably in both density and distribution in Li-and Na-layered cathodes. 20 We expect that controlling structural defects through high-energy ion radiation can offer an effective path toward tailoring electrochemical properties of battery materials. In addition, a Ni−Li antisite defect is universally observed in layer oxide cathodes during synthesis and electrochemical cycling, which hinders Li transport and reduces capacity.…”
Section: Recent Progress In Understanding Heterogeneity and Structura...mentioning
confidence: 99%
“…10 We also observed the evolution of microstructural defects in Li-and Na-layered cathodes under Kr ion irradiation and concluded that structural defects can be manipulated using a high-energy ion irradiation. 20 Therefore, manipulating the chemical and structural properties of electrode materials at the mesoscale can be an effective and promising approach to modulating battery performance. However, it is not trivial to characterize electrode properties at nanoscale or microscale, especially under operando/in situ conditions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Ion beams can also be used for implantation, 9 waveguide formation, 10 functionalization of interfaces and surfaces, or emulation of exposure to extreme radiation environments, such as outer space or nuclear reactors. [11][12][13][14] Post-irradiation examination (PIE) is typically conducted to examine the impact of irradiation on materials. Evaluating post-irradiation microstructural evolution can be done with a variety of microscopies from optical to electron, through compositional analysis with surface and bulk spectroscopies, and through a wide range of property testing platforms.…”
Section: Introductionmentioning
confidence: 99%
“…One such hurdle is the irreversible oxygen redox, which often leads to many unwanted phenomena such as electrolyte decomposition and gas evolution . The gas evolution can cause the collapse of the crystal structure leading to the formation of cation dense phase. , Alkali/alkaline ions in the transition metal layer that are responsible for triggering oxygen redox, play a dominant role in determining the oxygen redox reversibility. Bruce and co-workers have shown that Li loss from the transition metal layer of Na x Li y Mn 1– y O 2 at high states of charge leads to the formation of underbonded oxygen ions causing O 2 and CO 2 evolution .…”
mentioning
confidence: 99%